Detection of IP Covert Timing Channels - Konstantin Grigorievich Kogos; Mikhail Aleksandrovich Finoshin (Безопасность информационных технологий, 2015)
Covert timing channels became widespread with the increasing popularity of packet switching networks. Detection of these channels is the only approach to counter that does not lead to a decrease of channel’s capacity. Known methods of the IP covert timing channels detection were systematized. Detection methods based on the analysis of patterns in the distribution of inter-packet delays according to criteria such as alpha and beta errors, an ability of implementation were compared.